2015
DOI: 10.3892/ol.2015.4002
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A inhibits the growth of liver cancer Focus and SMMC-7721 cells

Abstract: Abstract. Liver cancer is one of the most common types of cancer, and hepatoma demonstrates a poor long-term prognosis. The present study reports that glaucocalyxin A (GLA), a natural product isolated from Rabdosia umbrosa, inhibits the growth of the liver cancer Focus and SMMC-7721 cell lines in a dose-and time-dependent manner. The present study revealed that GLA arrested the liver cancer cells at the G2/M stage of the cell cycle and led to decreased expression of caspase 3 and the cleavage of poly(adenosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Glaucocalyxin A (C 20 H 28 O 4 , MW: 332.44, Figure 2) Glaucocalyxin A dose-and concentration-dependently inhibited the growth of the liver cancer Focus and SMMC7721 cells. Mechanistic studies found induction of G2/M phase cell cycle arrest as well as increased expression of cleaved caspase-3 and PARP [55]. In MCF-7 and Hs578T breast cancer cells, glaucocalyxin A induced apoptosis, and G2/M phase arrest by increasing the expression of intrinsic apoptotic markers cleaved caspase-3, BAX, and p53, while decreasing BCL-2 expression.…”
Section: Glaucocalyxins a And Bmentioning
confidence: 95%
“…Glaucocalyxin A (C 20 H 28 O 4 , MW: 332.44, Figure 2) Glaucocalyxin A dose-and concentration-dependently inhibited the growth of the liver cancer Focus and SMMC7721 cells. Mechanistic studies found induction of G2/M phase cell cycle arrest as well as increased expression of cleaved caspase-3 and PARP [55]. In MCF-7 and Hs578T breast cancer cells, glaucocalyxin A induced apoptosis, and G2/M phase arrest by increasing the expression of intrinsic apoptotic markers cleaved caspase-3, BAX, and p53, while decreasing BCL-2 expression.…”
Section: Glaucocalyxins a And Bmentioning
confidence: 95%
“…Pharmacological studies have identified the bioactivities of Wangzaozins. For example, glaucocalyxin A has been widely studied for certain important biological activities, including antitumor [ 11 ], apoptosis induction [ 12 , 13 ], antibacterial, anti-oxidative, anticoagulative, antithrombotic, antifibrotic, immune, and antineuroinflammatory activities [ 5 , 14 , 15 ]. Wangzaozin A, specifically isolated from Wang Zao Zi and not from other Isodon species, has been proved to be effective in the treatment of pneumonia, lung abscess, and pulmonary tuberculosis when applied independently.…”
Section: Introductionmentioning
confidence: 99%
“…20(S)‐ginsenoside Rh2 obtained from steroid glycosides like Ginseng dose‐ and time‐dependently induced apoptosis by caspase‐3, caspase‐8, and caspase‐9 activation in NB4 cells after a 12‐h treatment 57 . Glaucocalyxin A, when tested for its apoptotic ability in multiple cell lines, demonstrated strong anticancer effects in liver cancer Focus (IC 50 : 2.70 µM), SMMC‐7721 (IC 50 : 5.58 µM), HepG2 (IC 50 : 8.22 µM), SK‐HEP1 (IC 50 : 2.87 µM), 58 MCF‐7 (IC 50 : 1.00 µM), Hs578T (IC 50 : 4.00 µM), 59 and HL‐60. Several examples illustrated the effectiveness of terpenoids in inducing cytostatic effects, apoptosis, and activating caspase signaling pathways in different cancer cell lines.…”
Section: Role Of Phytochemicals As Caspase Inducers: Natural Semisynt...mentioning
confidence: 99%